Linear hybrid cellular automata (LHCA) rule 90/150 based S-box - Roslan M.F.; Seman K.; Md Sayuti M.N.A.; Azni Hazlizan Ab Halim (Blue Eyes Intelligence Engineering and Sciences Publication, 2024)
Indexed by Scopus